2019
DOI: 10.4103/jpn.jpn_35_19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task-oriented activities based on neurodevelopmental therapy principles on trunk control, balance, and gross motor function in children with spastic diplegic cerebral palsy: A single-blinded randomized clinical trial

Abstract: Purpose:To examine the effects of task-oriented activities based on neurodevelopmental therapy (TOA-NDT) principles on trunk control, balance, and gross motor function in children with spastic diplegic cerebral palsy (SDCP).Materials and Methods:Forty-four children with SDCP, aged 7–15 years, were recruited to participate in the randomized clinical trial. After random allocation, twenty-two (n = 22) children with SDCP participated in TOA-NDT principles and twenty-two (n = 22) in conventional physiotherapy (CPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 27 publications
3
19
0
4
Order By: Relevance
“…In addition, the results of this study are consistent with clinical interventions reporting that a trunk protocol focused on dynamic co-activation of trunk flexors and extensors (based on neurodevelopmental therapy) improved gross motor function in children with spastic cerebral palsy [26][27][28]. Similarly, the same study results were reported in adult stroke patients [49].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the results of this study are consistent with clinical interventions reporting that a trunk protocol focused on dynamic co-activation of trunk flexors and extensors (based on neurodevelopmental therapy) improved gross motor function in children with spastic cerebral palsy [26][27][28]. Similarly, the same study results were reported in adult stroke patients [49].…”
Section: Discussionsupporting
confidence: 89%
“…However, in recent clinical trials, it has been reported that trunk control intervention based on neurodevelopmental treatment improves postural control, balance, and gross motor functions in children with CP more effectively than conventional treatments [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trunk instability is evident in spastic diplegic CP observed by oscillations in the center of pressure, altering the balance and further delaying gross motor function. The delay in gross motor function and altered balance lead to difficulty in performing activities of daily living and poor walking abilities 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The pooled ES of the three studies investigating the effectiveness of facilitation on activity level, using the GMFM as an outcome, was large but not significant (ES = 3.78, 95% CI [− 6.73-14.28]), as shown in the forest plot, Fig. 4a (Kerem & Livanelioglu, 2002;Sah et al, 2019;Tsorlakis et al, 2004). The pooled ES of the studies reporting outcomes with the PEDI for participation (Blauw-Hospers et al, 2011;Cameron et al, 2005) was medium (ES = 0.26, 95% CI − 1.32 to 1.84; Fig.…”
Section: Facilitation Of Activities and Movementsmentioning
confidence: 97%